FAKTOR PREDISPOSISI YANG MEMPENGARUHI KECEMASAN PADA IBU HAMIL PRIMIGRAVIDA DI PUSKESMAS POTA MANGGARAI TIMUR - odilia esem (STIKes CHMK, 2022)
Although pregnancy is a physiological process, most women still feel stress and panic during the pregnancy process which continues during labor and causes muscles to become stiff which ultimately causes excessive pain in pregnant women. During pregnancy, every woman experiences many changes, both physical changes and psychological changes. Changes in early pregnancy can affect the psychology of pregnant women. Based on World Health Organization (WHO) data in 2010 there were as many as 5% of women who were not pregnant experienced anxiety disorders, and there were about 8-10% of women during pregnancy experienced anxiety and experienced an increase to become pregnant. 12% at the time of delivery. In addition, based on another study also stated that there were about 67% of pregnant women who said they were a bit anxious at the time of delivery, then 12% said they were very anxious and 23% were not. The purpose of this study was to determine the predisposing factors that are worrying in primigravida pregnant women at Puskesmas Pota Manggarai Timur. The research method used is descriptive analytic method with a cross sectional design. The sample in this study were 54 primigravida mothers who were selected using inclusion criteria and using purposive sampling technique. Collecting data using a questionnaire. The results showed that most of the primigravida pregnant women experienced anxiety with the anxiety category of 96.3% and 3.7% who experienced anxiety in the panic category, then the results of the analysis showed that behavioral factors were the most influential regression factors on anxiety of primigravida pregnant women with a regression coefficient of 2.191. It is expected that primigravida pregnant women carry out examinations to determine the development of pregnancy and increase predisposing factors so that they do not experience anxiety during pregnancy and childbirth. Keywords: Predisposing Factors, Anxiety, Primigravida Pregnancy